Performance feedback and middle managers' divergent strategic behavior: The roles of social comparisons and organizational identification - Tarakci, Murat; Ateş, Nüfer Yasin; Floyd, Steven W.; Ahn, Yoojung; Wooldridge, Bill (Strategic Management Journal, 2018)
[Research Summary: What drives middle managers to search for new strategic initiatives and champion them to top management? This behavior—labeled divergent strategic behavior—spawns emergent strategies and thereby provides one of the essential ingredients of strategic renewal. We conceptualize divergent strategic behavior as a response to performance feedback. Data from 123 senior middle managers overseeing 21 multi-country organizations (MCOs) of a Fortune 500 firm point to social performance comparisons rather than historical comparisons in driving divergent strategic behavior. Moreover, managers' organizational identification affects whether they attend to organizational- or individual-level feedback. These results contribute to research on performance aspirations and strategy process by providing a multilevel, multidimensional framework of performance aspirations in middle management driven strategic renewal. Managerial Summary: Middle managers are essential actors in strategic renewal. Their unique positions offer insights into operations alongside knowledge of strategy. In contrast to typical assessments of managerial performance with reference to a prior year, this research shows that performance comparisons relative to peers and other organizational units better motivate managers' divergent strategic behavior. Our results also show that managers who identify with the firm are more attentive to organizational rather than individual performance discrepancies. Thus, our study unveils an important approach for organizations aiming to spark strategic renewal.]